Bis(propyl)-cognitin potentiates rehabilitation of treadmill exercise after a transient focal cerebral ischemia, possibly via inhibiting NMDA receptor and regulating VEGF expression. (September 2019) - Ke, Zheng; Hu, Shengquan; Cui, Wei; Sun, Jing; Zhang, Shaojie; Mak, Shinghung; Wang, Jiajun; Tang, Jing; Pang, Yuanping; Han, Yifan; Tong, Kaiyu
Abstract: Combination therapies may have greater efficacy compared with monotherapy in treating stroke. We investigated the molecular mechanisms by which the combination of bis(propyl)-cognitin, an uncompetitive antagonist of NMDA receptor, and treadmill exercise promote rehabilitation after ischemic stroke. Rats were distributed into 3 treatment groups: infarct/bis(propyl)-cognitin(drug only group, DO); infarct/treadmill exercise(exercise only group, EO); infarct/bis(propyl)-cognitin + treadmill exercise (drug + exercise group, DE). The DE group had further separated to 3 sub-groups to investigate the effects achieved by different time for drug administration (60 min before stroke (DE-60 m), 15 min (DE+15 m) and 60 min (DE+60 m) after stroke). Although all infarct groups improved over time, the combination of bis(propyl)-cognitin and treadmill exercise effectively enhanced motor recovery during 14-day intervention. Early drug intervention has a best recovery result, the DE+15 m group with drug intervention at 15-min after stroke had better motor recovery than DE+60 m, DO, EO and control groups. Both bis(propyl)-cognitin and treadmill exercise significantly elevated brain VEGF expression and decreased brain infarct volume at 14 day post-ischemia. Our study reveals that bis(propyl)-cognitin potentiated rehabilitation of treadmill exercise after ischemic stroke, possibly via regulating brain VEGF expression, indicating that the combination of NMDA receptor antagonists and exercise might be useful for stroke rehabilitation. Highlights: The combination effects of B3C and treadmill exercise in an MCAO model. The combination, particularly early drug intervention, has the best recovery result. The combination effects were achieved via inhibiting NMDAR and regulating VEGF.